Mediating Role of Employee Readiness to Change in the Relationship of Change Leadership with Employees' Affective Commitment to Change - Daud Yusuf Simanjuntak; Kusno Kusno; Ahmad Ansyari Siregar; Risdalina Risdalina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Joint assets are assets obtained by a husband and wife as long as they are bound by a marriage rope, or in other terms it is explained that gono-gini property is property obtained by means of syirkah between husband and wife which causes an association of one property with another other assets and cannot be separated or differentiated anymore. In this writing, the author conducts research using the type of empirical normative research, where the author combines library data such as books, laws, combined with field research based on facts obtained in the field. The legal consequences in a divorce, in this case what is most felt is every husband or wife regarding the issue of joint property. As for the division of joint property which in this case is carried out, if the husband or wife is divorced, then for that they can claim that their rights to the assets obtained can be owned. As for this case, according to the provisions contained in Article 37 of Law no. 16 of 2019 on the amendment to Law no. 1 of 1974 concerning Marriage, then regarding the distribution of joint property, it must be given to the parties concerned, which is the husband or the wife.after the establishment of a new policy by the management team.